Obstacle Crossing Differences Between Blind and Blindfolded Subjects After Haptic Exploration - Forner-Cordero, Arturo; Garcia, Valéria D.; Rodrigues, Sérgio T. [UNESP]; Duysens, Jacques (Taylor & Francis, 2016)
Little is known about the ability of blind people to cross obstacles after they have explored haptically their size and position. Long-term absence of vision may affect spatial cognition in the blind while their extensive experience with the use of haptic information for guidance may lead to compensation strategies. Seven blind and 7 sighted participants (with vision available and blindfolded) walked along a flat pathway and crossed an obstacle after a haptic exploration. Blind and blindfolded subjects used different strategies to cross the obstacle. After the first 20 trials the blindfolded subjects reduced the distance between the foot and the obstacle at the toe-off instant, while the blind behaved as the subjects with full vision. Blind and blindfolded participants showed larger foot clearance than participants with vision. At foot landing the hip was more behind the foot in the blindfolded condition, while there were no differences between the blind and the vision conditions. For several parameters of the obstacle crossing task, blind people were more similar to subjects with full vision indicating that the blind subjects were able to compensate for the lack of vision.
Keywords: blind; gait; obstacle crossing; toe clearance; visual information